Milk-clotting activity of recombinant bovine and camel chymosin for cow’s, goat’s and ewes’ milk - Akishev, Zh.; Aktayeva, S.; Shamsiyeva , Yu.; Tursunbekova, A.; Kalemshariv , B.; Tultabayeva, T.; Khassenov, B. (Eurasian Journal of Applied Biotechnology, 2023)
Goats and sheep were domesticated during the Neolithic Revolution. Since then, various breeds of goats and sheep have been bred, including dairy ones. In this work, we tested the milk-clotting activity of recombinant bovine (Bos taurus) and camel (Camelus bactrianus) chymosins in cow, goat, and ewe milk. The milk-clotting activity of recombinant bovine chymosin for cow’s, goat’s and ewes’ milk was 12 854 ± 0,61, 5385 ± 0,25 and 14 811 ± 0,72 U/mg. The activity of recombinant camel chymosin was higher by 29%-46% and amounted to 16 590 ± 0,82, 7850 ± 0,34 and 20 700 ± 0,85 U/mg. Proteolytic activity was 1679.97 ± 9.54 and 10 767 ± 54.56 U/mg for recombinant camel and bovine chymosins, respectively. With the recombinant camel chymosin, cheeses were obtained from cow’s, goat’s and ewes’ milk. The yield of cheese from cow’s, goat’s and ewes’ milk was 18.0%, 17.3% and 15.3%, respectively. The results indicate the prospects for the use of recombinant camel chymosin as the coagulation enzyme in the processing of cow’s, goat’s and ewes’ milk to cheeses.